Monkeypox (MPOX) in an HIV negative heterosexual male patient - Buendía-Flores, Ninoska Nelly (2023)
We present the case of a 28-year-old male patient, heterosexual, with negative HIV who developed an intense skin rash characterized by the presence of confluent vesicles, pustules, and umbilicated papules on the penis and pubic region with little spread to the rest of the body, without lymphadenopathy or systemic manifestations, four days after having sexual relations with an apparently healthy prostitute. The swabbing of the dermal lesions revealed the presence of MPOX virus DNA by real-time PCR. The immunological tests were the following: negative fourth-generation ELISA and Western Blot for HIV, IgM antibodies to herpes simplex1=1.2 U/ml, IgM antibodies to herpes simplex2=1.9 U/ml, IgM antibodies to varicella zoster=0.5 S/CO and negative FTA-ABS (IgM) for syphilis. The intensity of skin lesions on the penis and the need to perform tests to rule out MPOX in prostitutes are highlighted.